Spatial proximity and SWB a study across nations - Sureshkumar, Varsha; Gunasekar, Sangeetha; P, Balasubramanian (International Journal of Engineering and Technology, 2018)
Subjective wellbeing (SWB) has gained importance as a key indicator of an individual’s level happiness, as well as the happiness of a nation as a whole. This paper examined the influence of a spatial proximity variable like population density on the level of individual subjective wellbeing, along with established sociodemographic and economic variables. Respondent level data from 44 countries in Wave 6 of the World Values Survey was used to perform a cross country TOBIT analysis. Results showed that spatial proximity at the respondent level has a positive and significant impact on the SWB of individuals, with the inclusion of population density adding to the explanatory power of our model. This study relies on respondent level information from the World Values Survey about spatial proximity, whereas other studies have utilized country level statistics.